2002
DOI: 10.1590/s0037-86822002000500016
|View full text |Cite
|
Sign up to set email alerts
|

Um caso de parasitismo por Rhabditis sp em criança natural de Goiânia, Goiás, Brasil

Abstract: Relata-se um caso de parasitismo por Rhabditis sp em criança com cinco meses de idade procedente do Estado de Goiás, Brasil. O quadro clínico mostrou inicialmente diarréia com fezes líquidas esverdeadas e posteriormente sanguinolentas. O exame parasitológico de fezes revelou a presença de larvas e adultos de Rhabditis sp. Após o uso de thiabendazole houve melhora no quadro clínico e cura. Os autores chamam atenção para a importância de se estabelecer o diagnóstico diferencial entre Strongyloides e Rhabditis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
7

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 4 publications
0
9
0
7
Order By: Relevance
“…These were the places that had the parcels with the largest amount of garbage and decomposing organic matter. Nematodes of the genus Rhabditis are free-living and may be naturally found in humid places with decaying organic matter (Campos et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These were the places that had the parcels with the largest amount of garbage and decomposing organic matter. Nematodes of the genus Rhabditis are free-living and may be naturally found in humid places with decaying organic matter (Campos et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Rhabditis nematodes were found in the faeces of a child with abdominal disorders, in the state of Goiás, Brazil (Campos et al, 2002). The possibility of the presence of nematodes in humans can be considered when there is manipulation of the environment and subsequent contamination, once the species is free life and the mollusks can serve as carriers of these nematodes (Anderson et al, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…Nestes locais foi observada muita matéria orgânica em decomposição, o que poderia favorecer um grande número de registro dos hospedeiros. A população de nematoides e de rotíferos e, consequentemente, de seus parasitas geralmente é alta em ambientes ricos em matéria orgânica (Neweu-Lemaire 1936, Campos et al 2002.…”
Section: Comentáriosunclassified
“…Neste estudo, houve maior número de observação de parasitismo em nematoide (Rhabditis sp), o que concorda com o esquema proposto por Dick (1995Dick ( , 2001b 1981, Mateus Júnior 1985, Campos et al 2002.…”
Section: Comentáriosunclassified
“…In terms of public health, A. fulica is a potential intermediate host of nematodes of medical importance, such as Angiostrongylus costaricensis Morera and Céspedes, 1971 and Angiostrongylus cantonensis (Chen, 1935), related to the abdominal and meningocerebral angiostrongyliasis (Thiengo et al, 2007;Maldonado Júnior et al, 2010). It can be also a potential both an intermediate and paratenic host of some parasites of wild animals species of Aelurostrongylus Cameron, 1927 (Thiengo et al, 2008;Oliveira et al, 2010) could parasite lung both domestic and wild cats (Ribeiro and Lima, 2001), Rhabditis Dujardin, 1845, that lodge in the external auditory canal of cattle, causing otitis (Martins Júnior, 1985;Campos et al, 2002;Thiengo, 2009;Barbosa et al, 2016) and Strongyluris Mueller, 1894, which are intestinal parasites mainly found in lizards (Kohn et al, 1973;Vicente et al, 1993;Rocha and Vrcibradic, 2003).…”
Section: Introductionmentioning
confidence: 99%